Classroom as a playground - Práger, Libor; Řeřicha, Václav (e-Pedagogium, 2020)
In the last sixty years the literacy environment based on alphabetic technology has almost completely transcended into the electronic environment based on digital technology. The traditional literacy-based classrooms and school libraries as centres of knowledge and education may have still retained their physical existence but have lost their foundation and purpose. The changes brought about by the digital environment have forced the traditional classroom and its literate environment emphasizing the importance of speaking, reading and writing to search for new meaning. While most educators are still clutching to the straw of the traditional literacy-based classroom by inventing more and more amusing presentations, the signs of traditional classroom's crisis are more and more visible. The physical classroom has competed and has lost to virtual reality which is instantaneous, transferable and imminently involving, the traditional school with textbooks seems to be a museum relic to contemporary "digital natives". The contemporary research among university students confirms the notion that modern curricula should offer a vision of a school which is not a centre of obsolete knowledge distribution but a playground where the students learn the rules of the games that will be played in the 21st century.
Keywords: Literacy-based classroom; digital environment; tradition; transition; socialization.